Od powieści filozoficznej do teatru (post)epickiego? ’Kosmos’ Witolda Gombrowicza w inscenizacji Jerzego Jarockiego - Gołos-Dąbrowska, Katarzyna (Załącznik Kulturoznawczy, 2021)
The aim of the article is to present the way in which Jerzy Jarocki transforms Witold Gombrowicz’s Cosmos into a theatrical script. The director does not try to extract a purely dramatic form from the novel, but creates a dramatization that takes into account the epic elements of the work. He proves with his realization that the producer does not have to deconstruct the work or even modernize it in order to introduce a discussion about the work and its readings to the stage. The scenography (created by Jerzy Juk-Kowarski) is extremely important in the context of the realization of the Cosmos, which allows the creators to place the staging in a specific philosophical context, enlivens the recipient’s imagination and, in a way, forces an active reception of the work.